Literature Review: The Relationship Between Nurses’ Workload And The Performance Of Staff Nurses In Inpatient Wards - Junaina Ridwan; Wan Eliza Susana; Erika Erika (Jurnal Ners, 2026)
Introduction: Nurses’ workload is an important factor influencing the quality of nursing performance in hospitals. Excessive workload may affect nurses’ physical and psychological conditions, including fatigue, work stress, burnout, and decreased work motivation, which ultimately impact the quality of patient care. This issue is important because nurses are healthcare professionals who maintain direct and continuous contact with patients during inpatient care. Imbalanced workload may also increase the risk of medical errors, reduce patient satisfaction, and hinder the achievement of hospital service standards. Objective: To analyze the relationship between workload and the performance of staff nurses in inpatient wards through a literature review. Methods: This study employed a literature review approach by searching articles from Google Scholar, PubMed, and SINTA databases using keywords related to workload and nurse performance. The inclusion criteria included quantitative studies published between 2019 and 2025 discussing workload and nurse performance. A total of 12 articles were analyzed narratively. Results: Most studies demonstrated a significant relationship between workload and nurse performance. High workload tended to reduce performance through increased fatigue and work-related stress. In addition, organizational factors such as staffing availability, work systems, and task distribution also influenced nurse performance. Conclusion: Workload has a negative effect on nurse performance. Therefore, optimal workload management is necessary to improve the quality of healthcare services and patient safety.